The impact of parental migration patterns, timing, and duration on the health of rural Chinese children - Wang, Feng; Wang, Ying; Liu, Shumei; Cui, Linlin; Li, Feimeng; Wang, Xiaohe (Frontiers in Public Health, 2024)
Background: Parent-child separation raises concerns for the well-being of 69 million left-behind children (LBC) in China. However, the effects of parental migration status, timing of migration, and migration duration on the health of children remain unclear. This study aims to explore the association between different parent-child separation experience and a range of health outcomes in rural Chinese children.Method: A sample of 2355 students, grades 5 to 8, from two provinces in China were recruited.Standardized self-report instruments collected data on demographics, separation status, and children's health conditions.Results: Full data were available for 274 children with both parents currently migrating (BLBC), 638 children with one parent currently migrating (SLBC), 658 children with parents previously migrated (PLBC) and 785 children with non-migrating parents (NLBC). Regression model results showed that, compared to the NLBC group, BLBC and PLBC exhibited lower self-rated health (p<0.05), higher depression (p<0.05), and higher rates of non-suicidal self-injury behaviors (p<0.05) and suicidal ideation (p<0.05). Children who experienced parental separation before the age of three were at a higher risk for four health indicators. Additionally, children left behind by parents for more than 7 years had significantly worse health outcomes.Conclusions: Children who have experienced both current and previous parental migration, as well as earlier parental migration age and longer migration duration, are at a disadvantage in terms of health.These findings highlight the need for targeted interventions focusing on the most vulnerable children.